Voices of decolonization a brief history with documents - Shepard, Todd (The Bedford series in history and culture, 2015)
PART ONE Introduction: Decolonization, from Unimaginable to Inevitable -- What Is Decolonization? -- The Varieties of Imperialism -- Interwar Empires: Crisis and Consolidation, 1918--1937 -- World War II: Decolonization Becomes Imaginable -- New International Connections -- European Efforts to Reinvent Overseas Colonialism -- The Cold War, Local Collaborators, and the Slowing Pace of Change -- The Rise of Anticolonial Radicalism -- The International Politics of Decolonization -- Algeria's Decolonization -- The Legacies of Decolonization -- PART TWO The Documents -- 1. 1945--1947: Decolonization Becomes Imaginable -- 1. Winston Churchill, "Hands Off the British Empire," December 31, 1944 -- 2. United Nations, United Nations Charter: Preamble and Declaration concerning Non-autonomous Territories, June 26, 1945 -- 3. Ho Chi Minh, Declaration of Independence of the Democratic Republic of Vietnam, September 2, 1945 -- 4. An Appeal of the Vietnamese Bishops in Favor of the Independence of Their Country, September 23, 1945 -- 2. Defining New International Connections -- 5. Fifth Pan-African Congress, The Challenge to the Colonial Powers, 1945 -- 6. UNESCO, The Statement on Race, July 1950 -- 7. Alfred Sauvy, Three Worlds, One Planet, August 14, 1952 -- 8. First Afro-Asian Conference, Final Communique, April 24, 1955 -- 9. Richard Wright, The Color Curtain: A Report on the Bandung Conference, 1956 -- 10. Joseph Kirira and Josiah Kariuki, Song of Africa (Kenyan Song), 1957 -- 3. From Possibilities of Independence to Expectations of Liberation -- 11. Song for Murang'a Women (Kenyan Song), ca. 1950 -- 12. Historical Survey of the Origins and Growth of Mau Mau, 1950, 1960 -- 13. Historical Survey of the Origins and Growth of Mau Mau, 1952, 1960 -- 14. Gamal Abdel Nasser, Egypt's Liberation: The Philosophy of the Revolution, 1955 -- 15. The Shin Bet, The Minorities in Israel, February 26, 1958 -- 16. Georgios Grivas, Report Addressed to Michail Christodolou Mouskos, May 23, 1955 -- 17. Oath of the National Organization of Cypriot Combatants, 1955 -- 4. The Triumph of Anticolonialism -- 18. Mohammed Dib, The Fire, 1954 -- 19. National Liberation Front, Proclamation, November 1, 1954 -- 20. Francois Mitterrand, Speech in Response to FLN Actions, November 12, 1954 -- 21. Slimane Azem, Locust, Leave My Country (Berber Song), 1955 -- 22. Muslim Population of Tebessa, Letter to Robert Lacoste, July 1956 -- 23. Rene Massigli, French Intelligence Analysis of British Public Opinion on the Algerian Conflict, December 1956 -- 24. Charles de Gaulle, Presidential Press Conference, April 11, 1961 -- 25. Frantz Fanon, The Wretched of the Earth, 1961 -- 26. Visitor, Lift Up the Torch of United Africa, April 12, 1958 -- 27. Eric Williams, Massa Day Done, March 22, 1961 -- 5. The Contagion of Independence -- 28. Conscience Africaine, Manifesto for Belgian Congo, July 1956 -- 29. ABAKO, Counter Manifesto for Belgian Congo, August 23, 1956 -- 30. Harold Macmillan, "Wind of Change" Speech, February 3, 1960 -- 31. Ingrid Jonker, The Child Who Was Shot Dead by Soldiers at Nyanga, 1960 -- 32. United Nations General Assembly, Declaration on the Granting of Independence to Colonial Countries and Peoples, December 14, 1960 -- 33. Alvim Pereira, Ten Principles, 1961 -- 34. Celina Simango, Speech at the International Women's Congress in Moscow, June 1963 -- 35. Amilcar Cabral, Anonymous Soldiers for the United Nations, December 12, 1962 -- 36. Zhou Enlai, Conversation with S. V. Chervonenko, April 20, 1965 -- 37. Fayez A. Sayegh, Zionist Colonialism in Palestine, 1965 -- 38. Claudia Jones, The Caribbean Community in Britain, 1964 -- 39. Kwame Nkrumah, Neo-Colonialism: The Last Stage of Imperialism, 1965 -- APPENDIXES -- A Chronology of the Era of Decolonization (1937--1965) -- Questions for Consideration